Hubungan Antara Lama Sakit Dengan TingkatDistress Pada Pasien Diabetes MellitusDi Rumah Sakit Islam Surakarta - Permana, Yudha Indra; , Arum Pratiwi, S.Kp., M.Kes (2017)
DM (Diabetes Mellitus) or diabetes is one type of chronic disease, the number of events is increasing from year to year. Their excessive concern if the illness turns out not heal a factor onset of distress in patients with diabetes mellitus. Older diabetic patients experienced pain in one side of the impact on the increase in patients 'knowledge about the handling of DM but the other relates to the decline in the quality of diabetes patients' health. This study aims to determine the relationship between the old hospital to the level of distress in patients with diabetes mellitus in Surakarta Islamic Hospital. This research is quantitative descriptive method correlative, where researchers tried a long relationship with the level of distress ill patients with diabetes mellitus with cross sectional approach. The study population was patients with diabetes mellitus in the Islamic Hospital (RSI) Surakarta. The latest data throughout 2015 there were a total of 198 cases of patients with DM is the average case is 17 patients a month. The research sample of 30 patients obtained by accidental sampling technique. Data collection research using questionnaires and data analysis using product moment correlation test. Conclusion of the study is longer ill patients mostly over 10 years old, the level of distress of patients are mostly mild, while the components distress of the most dominant of the onset of distress to the patient is the emotional burden and response to health workers, and there is a relationship between a long illness at the level of distress in patients with diabetes mellitus in Surakarta Islamic Hospital (p-value = 0.001) where the longer sick, the lower the level of distress.